Normative values and a new predicted model of exercise blood pressure in young athletes. Issue 1 (January 2023) - Mascherini, Gabriele; Galanti, Giorgio; Stefani, Laura; Izzicupo, Pascal
Abstract: Objectives: Assessing the systolic and diastolic blood pressure during acute physical exertion can allow the discovery of many cardiovascular diseases even at a young age. However, this response depends on the age, sex of the subject, and the modality of the graded exercise test. This study aims to provide sex-and age-related normative values of peak and recovery blood pressure performance and to develop a predicted model of systolic and diastolic blood pressure peak in young athletes. Design: Retrospective-study. Methods: We analyzed 8224 young athletes (5516 males and 2708 females) aged between 8 and 18. Anthropometric and blood pressure parameters related to the effort are reported. Then, according to sex, graded exercise test modality, and age were calculated 1) the fifth, tenth, fiftieth, ninetieth, and ninety-fifth percentiles for the systolic and diastolic blood pressure at peak and after 1 min of recovery and 2) predictive equations of systolic and diastolic blood pressure at the peak. Results: Younger athletes show lower peak blood pressure values, gradually increasing as they age. Males showed higher peak systolic blood pressure values starting at 12–13 years on the cycle ergometer and 10–11 years on the treadmill, while there was no difference in peak diastolic blood pressure values. Conclusions: Sex, age, and the specificity of the movement performed must be considered in assessing the blood pressure response in the young population. In addition, providing reference values and predictive equations of blood pressure response to acute physical exertion may allow for a better functional assessment of young athletes.